"Oh, I like Your Accent": Perceptions and Evaluations of Standard and Non-standard Accented English Speakers. (4th May 2022) - Acheme, Doris E.; Cionea, Ioana A.
Abstract : This study examined the evaluation of standard-accented English (SAE) and nonstandard accented English (non-SAE) speakers in the United States. Results of an experiment ( N = 670) manipulating accent, nationality/L1 introduction, and speaker sex revealed main effects for accent on the evaluation of status, solidarity, and dynamism, and a main effect of speaker sex on solidarity. Additionally, an interaction effect between accent and nationality/L1 introduction on status and dynamism was found, as was an interaction effect of accent and speaker sex on dynamism. These results suggest complexity in the evaluation of non-SAE speakers and are discussed in relation to language attitudes and intergroup communication.